Assessment of Electromagnetic Absorption towards Human Head Using Specific Absorption Rate - Abdul Rashid O. Mumi; R. Alias; Jiwa Abdullah; Samsul Haimi Dahlan; Jawad Ali (Institute of Advanced Engineering and Science, 2018)
This paper presents a compact square slot patch antenna characterstics for wireless body area network (WBANs) applications.The assessment of the effects of electromagnetic energy (EM) on the human head is necessary because the sensitivity of human head to high radiation level. Although, structuring of low EM antennas is a major problem in the improvement of portable device and reducing the size of of the antenna is a major concern. However, performance of antenna reduces when antenna operates near human body which is lossy and complex in nature. The proposed antenna operates at 5.8GHz of the ISM Band for WBAN applications. The antenna has been designed and simulated with two different types of multilayer human head phantoms to characterize the antenna near the human head.The multilayer head phantom is constructed by five layers tissues head model using CST Microwave studio. Therefore, antenna with spherical phantom has the highest SAR value 0.206 W/Kg, while antenna with cubical phantom contributed the lowest SAR value of 0.166 for 10 g tissue at 5.8 GHz frequency exposed, whereas, the antenna with cubical phantom and spherical phantom have gain of 6.46 dBi and 6.2 dBi GHz respectively. It was observed that antenna performance significantly increased. The presented prototype has a potential to work for ISM applications.